John Dewey and Daoist thought - Behuniak, James (State University of New York, 2019)
"In this expansive and highly original two-volume work, Jim Behuniak reformulates John Dewey's late-period "Cultural turn" and proposes that its next logical step is an "intra-Cultural philosophy" that goes beyond what is commonly known as "comparative philosophy." Each volume models itself on this new approach, arguing that early Chinese thought is poised to join forces with Dewey in meeting an urgent cultural need: namely, helping the Western tradition to correct its outdated Greek-medieval assumptions, especially where these result in pre-Darwinian inferences about the world. Relying on the latest findings in Chinese philosophy, these volumes establish "specific philosophical relationships" between Dewey's ideas and early Chinese thought for this purpose, showing how together they can assist us in getting our thinking "back in gear" with the world as it is currently known through the biological, physical, and cognitive sciences. Volume One: Dao and Nature engages Dewey with themes generally associated with "Daoism," and includes discussion of the organization of organic form, teleology, cosmology, knowledge, the body, and technology. Volume One thus works to establish "Chinese natural philosophy" as an empirical framework in which to consider the cultural-level phenomena examined in Volume Two: Dao and Culture"-- Provided by publisher
Keywords: Dewey, John, -- 1859-1952 -- Knowledge -- Taoist philosophy.; Dewey, John, -- 1859-1952 -- Travel -- China.; Dewey, John, -- 1859-1952; Taoist philosophy.; Philosophy, Chinese.; Philosophy, Comparative.; East and West.; Philosophie taoïste.; Philosophie chinoise.; Philosophie comparée.; Eastern.; Pragmatism.; Movements.; PHILOSOPHY.; Confucianism.; RELIGION.; East and West; Philosophy, Chinese; Philosophy, Comparative; Taoist philosophy; Travel; China; Electronic books.